• $(A^*)^*=|A|^{n-2}A(A为可逆方阵)$。

$$ A^*(A^*)^*=|A^*|E $$

$$ \Rightarrow (A^*)^{-1}A^*(A^*)^*=(A^*)^{-1}|A^*|E $$

$$ \Rightarrow (A^*)^*=(A^*)^{-1}|A^*|E\tag{1} $$

$$ AA^*=|A|E $$

$$ \Rightarrow|AA^*|=||A|E| $$

$$ \Rightarrow|A||A^*|=|A|^n $$

$$ \Rightarrow|A^*|=|A|^{n-1}\tag{2} $$

$$ A^*=|A|A^{-1} $$

$$ \Rightarrow (A^*)^{-1}=(|A|A^{-1})^{-1} $$

$$ \Rightarrow (A^*)^{-1}=|A|^{-1}A\tag{3} $$

$$ (1),(2),(3)\Rightarrow (A^*)^*=|A|^{n-2}A\tag{4} $$

  • $(kA)^*=k^{n-1}A^*(A为可逆方阵)$

$$ (kA)(kA)^*=|kA|E $$

$$ =|kA|(kA)^{-1} $$

$$ =k^n|A|k^{-1}A^{-1} $$

$$ =k^{n-1}|A|A^{-1} $$

$$ =k^{n-1}A^*\tag{5} $$

  • $(A^*)^{-1}=(A^{-1})^*(A为可逆方阵)$

$$ (A^*)^{-1}=(|A|A^{-1})^{-1} $$

$$ =|A|^{-1}A $$

$$ =|A|^{1-n}|A|^{n-2}A\tag{6} $$

$$ (4),(5),(6)\Rightarrow (A^*)^{-1}=|A|^{1-n}(A^*)^* $$

$$ =(|A|^{-1})^{n-1}(A^*)^* $$

$$ =(|A|^{-1}A^*)^* $$

$$ =(A^{-1})^* $$

Last modification:June 24th, 2021 at 08:17 pm
博客维护不易,如果你觉得我的文章有用,请随意赞赏